EGR1 Promotes Craniofacial Bone Regeneration via Activation of ALPL⁺PDGFD⁺ Periosteal Stem Cells - Yang Li; Dazhuang Lu; Fanqing Xu; Jun Yang; Dong Li; Chenlong Yang; Xin Chen; Xu Wang; Jia Qing; Hui Zhang; Yingfei Zhang; Fuchou Tang; et al. (Advanced Science)
Abstract Oral and craniofacial bone regeneration remains challenging due to unique anatomical and functional demands. Rodent models have limited translational value because of significant structural differences from humans. The study reveals high similarity in calvarial periosteal cell composition between miniature pigs and humans at single‐cell resolution. ALPL+PDGFD+ (AP+) cells are identified as distinct calvarial periosteal stem cells (PeSCs) that possess self‐renewal and differentiation potential in both swine and human calvarial periosteum. Postnatally, AP+ PeSCs exhibit reduced activity compared to their embryonic counterparts, with EGR1 recognized as a crucial factor for their activation. Upon activation, these cells effectively facilitate the repair of craniofacial bone injuries. EGR1 regulates PeSCs development by modulating BMP signaling through its Znf2 domain and activating these cells via the CTNNB1/WNT10B pathway through its Znf2/3 domains in response to injury. The validation of the findings using human cranial periosteal samples from various developmental stages (embryonic and adult) further supports the results obtained from large animal experiments, providing a solid scientific foundation for the clinical application of AP+ cranial periosteal stem cells. Additionally, targeting specific EGR1 domains for in situ activation of PeSCs offers a promising strategy for enhancing bone regeneration.